2020
DOI: 10.1002/jctb.6510
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot synthesis of meso‐microporous ZSM‐5 and its excellent performance in VOCs adsorption/desorption

Abstract: BACKGROUND: The meso-microporous ZSM-5 is used for treating the complicated industrial organic waste gas, owing to its good hydrophobicity, excellent thermal and hydrothermal stability, and lower mass transfer resistance than conventional ZSM-5, resulting in its great adsorption property for volatile organic compounds (VOCs). In this paper, different types of meso-microporous ZSM-5 (NZ5, MZ5) were prepared using the templates and then characterized by X-ray diffraction, infrared spectroscopy, transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…[4][5][6] In particular, the pore distribution in ACMs can be regulated to facilitate OVOCs diffusion and to balance adsorption and desorption processes. 7,8 For instance, Wang et al demonstrated that a well-developed hierarchical pore structure could promote the desorption efficiency of ethyl acetate (EA) on ACMs; the desorption efficiency remained as high as 93% after several cycles of adsorption and desorption. 9 In general, ACMs with a controlled and homogeneous pore structure can provide good porosity for interfacial interactions by maintaining an interlaced carbon-skeleton structure that makes the most of the surface area available for the mass transfer that underpins adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In particular, the pore distribution in ACMs can be regulated to facilitate OVOCs diffusion and to balance adsorption and desorption processes. 7,8 For instance, Wang et al demonstrated that a well-developed hierarchical pore structure could promote the desorption efficiency of ethyl acetate (EA) on ACMs; the desorption efficiency remained as high as 93% after several cycles of adsorption and desorption. 9 In general, ACMs with a controlled and homogeneous pore structure can provide good porosity for interfacial interactions by maintaining an interlaced carbon-skeleton structure that makes the most of the surface area available for the mass transfer that underpins adsorption.…”
Section: Introductionmentioning
confidence: 99%